TRANSFORMASI STRATEGI BISNIS PERBANKAN KONVENSIONAL MELALUI INOVASI, KEBERLANJUTAN, DAN PENGUATAN SDM DI ERA DIGITAL - Hasanudin, Hasanudin; Faeni, Dewi Puspaningtyas (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze the transformation of conventional banking business strategies in the digital era, focusing on service innovation, sustainability practices, and human resource development. The research employs a qualitative descriptive approach by examining secondary literature from journals, industry reports, and official documents, as well as reviewing real practices in several banks in Indonesia. The findings indicate that digitalization of banking services significantly enhances operational efficiency, customer satisfaction, and loyalty, while implementing sustainability practices through Green Human Resource Management and Corporate Social Responsibility strengthens bank reputation and social legitimacy. Human resource development through digital competence enhancement, continuous training, and adaptive leadership proves to be a critical mediator that accelerates transformation and reduces resistance to change. These results emphasize that successful transformation of banking business strategies relies not only on technology adoption but also on integrating sustainability principles and enhancing human resource quality. Conceptually, a holistic transformation improves bank competitiveness and resilience, supports financial sector stability and national economic development, and provides practical guidance for banks in formulating adaptive and sustainable strategies.